Antecedents of attitude and their impact on behavioral intention in the staycation context - Zhang, Yating; Shen, Huawen; Xu, Jiajia; Qian, Stella Fang (Frontiers in Psychology, 2022)
The year 2020 and 2021 have been decimated by the pandemic, leading to outbound vacations largely scrapped. Staycation, a typical domestic journal, has then been adopted by those who are tired of self-isolation for so long. This study aims to explore and assess the drivers exerting impact on attitude of tourists toward staycation and the interrelationship among the research constructs is also examined. A quantitative analysis is employed for evaluating the roles of reduced risk perception, benign envy, and perceived benefits as they exert the effect on attitude toward staycation. An online questionnaire survey was used, and a total of 213 samples were collected from target respondents in Hong Kong, which were still under lockdown at the time of the study. The results of the study showed that reduced risk perception, benign envy as well as perceived benefits will influence tourists’ attitude toward staycation. The managerial and theoretical implications of the results are discussed based on the significant relationships identified in the study.